DEVELOPMENT OF TECHNOLOGY FOR CREATION OF EFFECTIVE VIBRATION SIEVES IN SELECTION OF INERT MATERIALS - Shavkidinovich, Toirov Murtoza; Askarhodjaev, Tulkin Ishanovich; Akbarova, Nigora Alimdjanovna; Reymbaeva, Sanabar Rejepbaevna (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with the operation of electric, compressed air vibrating spring sieves for the construction and repair of highways, sorting of coal mined in coal mines, possibility of achieving energy savings in the sorting of special sands imported for molds in the shops for the smelting of metals and casting of machine parts.